Same-sex Marriage: Principle Versus Practice. (12th December 2018) - Hull, Kathleen E
Abstract: This article uses in-depth interview data to examine the meanings of marriage for lesbian, gay, bisexual, transgender, and queer (LGBTQ) people in the US context. The politics of recognition and rights consciousness provide the theoretical frames for the study. The interview data indicate broad support for legal recognition of same-sex marriage among LGBTQ individuals, but more mixed views of marriage as a social institution and uneven personal aspirations to marry. Respondents fall into three broad categories: marriage-positive, marriage-ambivalent, and marriage-negative. The fact that LGBTQ respondents favour marriage more in principle (as a right) than in practice (as an actual social institution) suggests that marriage holds multiple meanings for them. I discuss these meanings in relation to the politics of recognition and the political effects of rights. I conclude that the tension between marriage in principle versus practice signals both a desire for recognition and a critical perspective on law.